An estimated 11,000 rice and cassava farmers in Cambodia are using agricultural advisories based on the seasonal forecast with support of Local Technical Agro-climatic Committees - Swaans, Cornelis P.M. (Bioversity International and the International Center for Tropical Agriculture, 2023)
An estimated 11,000 rice and cassava farmers from 23 Agri-cooperatives in Battambang and Kampong Speu provinces used the agroclimatic advisories in their planning and decision-making for better risk management. DeRISK SE Asia introduced the Local Technical Agroclimatic Committee (LTAC) approach in Cambodia to co-develop seasonal agroclimatic advisories based on seasonal forecasts with different type of stakeholders in two target provinces. The advisories were disseminated through multiple channels, including printed bulletins, Telegram, the SESAME mobile application, and face-to-face communication. The Local Technical Agroclimatic Committees (LTACs) are established at the provincial level to co-produce agroclimatic advisories that are tailored to the local context. The committees include relevant partners and stakeholders, such as the Provincial Department of Agriculture, Forestry, and Fisheries (PDAFF), and Provincial Department of Water Resources and Meteorology (PDoWRAM), agriculture technical experts from District Agriculture Offices (DAO), commune authorities and agri- cooperatives leaders. The advisories are based on Crop Decision Trees for rice and cassava that provide specific information on crop stages, agricultural practices, climate risk and response strategies under different climate scenarios. Agroclimatic advisories based on seasonal forecasts are disseminated to farmers via multiple communication channels: the distribution of printed bulletins during commune-level meetings, farmer interaction in villages by the leaders of agri- cooperatives and local authorities, and the installation of printed posters in public spaces. Farmer leaders and local authorities also immediately receive seasonal forecasts and agroclimatic advisories using digital channels, such as the SESAME application and Telegram. As a result, approximately 11,000 rice and cassava farmers, including 745 leaders of agricultural cooperatives and commune authorities, applied agroclimatic advisories for crop planning and decision-making. Farmers use agroclimatic advisories for seed varieties selection, land preparation, planting methods, water management, pest control, and harvesting date differently for wetter and drier climate conditions. This assisted the farmers in coping with potential climate-related risks such as excessive rainfall, flooding, drought, and pest infestation. For planting, farmers choose rice seed and cassava crop varieties that are tolerant to adverse climate conditions such as wetter or drier than normal scenarios. Different planting methods are utilized, such as broadcasting wet rice seed (direct-seeding) in wetter climatic conditions and broadcasting dry rice seed in drier climate conditions. Rice field dikes and drainage systems are constructed for enhanced water management, and farmers have improved their pest and disease control measures. For example, farmers restrict the application of nitrogen fertilizer and the amount of water released from their rice fields when the rice blast disease is increasing under wetter than normal scenarios. Farmers can better plan and manage their farms to avoid climate risks because they have improved access and enhanced understanding of the importance of seasonal forecasts and agroclimatic advisories.